2012
DOI: 10.3109/09638288.2012.689919
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of individualized satisfaction score in aid for decision-making in occupation choice

Abstract: The Japanese version of the ADOC is a valid and reliable instrument for measuring client satisfaction with individualized occupational performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…Subsequently, the participants rated their satisfaction with each activity using a scale of 1-5 (1: very dissatisfied, 5: very satisfied). The reliability and validity of individualized satisfaction score in ADOC has been reported [33]. Furthermore, participants rated their performance on a scale of 1-10 (1: with great difficulty, 10: perfectly).…”
Section: Meaningful Activitiesmentioning
confidence: 99%
“…Subsequently, the participants rated their satisfaction with each activity using a scale of 1-5 (1: very dissatisfied, 5: very satisfied). The reliability and validity of individualized satisfaction score in ADOC has been reported [33]. Furthermore, participants rated their performance on a scale of 1-10 (1: with great difficulty, 10: perfectly).…”
Section: Meaningful Activitiesmentioning
confidence: 99%
“…Occupational therapy evaluation and interventions should be based on an occupation (occupation-based approach) that includes purposeful and meaningful activities for an individual and the social context, rather than focusing on impairments or body structure (impairment-based approach) [8,9]. Recently, we developed an iPad (Apple Inc, Cupertino, CA, USA) application called the Aid for Decision-making in Occupation Choice (ADOC) to promote shared decision-making in activities and participation level (occupation)-based goal setting by choosing from illustrations describing daily activities [10,11]. Our case studies showed that older inpatients and the occupational therapist could identify meaningful activities using the ADOC, even if they had aphasia[12] or dementia [13](Mini-Mental State Examination [MMSE] >8 points [14]).…”
Section: Introductionmentioning
confidence: 99%
“…Limited research was found that addressed current mobile app-based devices, such as smartphones and handheld tablets including iPads and iPods. Two studies were found that utilized iPad in applied research during the occupational therapy process (Tomori, Saito, et al, 2012;Tomori, Uezu, et al, 2012). One study was found that utilized the iPad as a video-modeling tool for social participation, self-cares, and play skills (Cardon, 2012).…”
Section: Mobile App-based Devices As Evaluation and Interventionmentioning
confidence: 99%
“…An assessment-based app for the iPad, the Aid for Decision-making in Occupation Choice (ADOC) has been the subject of much research in Japan (Tomori, Saito, et al, 2012;Tomori, Uezu, et al, 2012). The ADOC is used as a goal-setting tool between client and occupational therapist by allowing the client to express needs and wants through images displayed on the iPad.…”
Section: Mobile App-based Devices As Evaluation and Interventionmentioning
confidence: 99%
See 1 more Smart Citation